Neonatal Thymulin Gene Therapy Prevents Ovarian Dysgenesis and Attenuates Reproductive Derangements in Nude Female Mice - Reggiani, Paula Cecilia (2012)
Congenitally athymic (nude) female mice show severe ovarian dysgenesis after puberty, which seems to be consequential to a number of neuroendocrine derangements described in these mutants. Thus, considerable evidence suggests that thymulin, a thymic peptide, may be involved in thymus-pituitary communication. In order to clarify the relevance of thymulin for the maturation of the female reproductive system, we assessed at hypothalamic, pituitary, ovarian, and uterine level the preventive action of neonatal thymulin gene therapy (NTGT) on the changes that typically occur after puberty in congenitally athymic female mice. We injected (im) an adenoviral vector harboring a synthetic DNA sequence encoding a biologically active analog of thymulin, metFTS, in newborn nude mice (which are thymulin deficient) and killed the animals at 70?71 d of age. NTGT in the athymic mice restored the serum thymulin levels. Morphometric analysis revealed that athymic nudes have reduced numbers of brain GnRH neurons and pituitary gonadotropic cells as compared with heterozygous controls. NTGT prevented these changes and also rescued the premature ovarian failure phenotype typically observed in athymic nude mice (marked reduction in the number of antral follicles and corpora lutea, increase in atretic follicles). Serum estrogen, but not progesterone, levels were low in athymic nudes, a reduction that was partially prevented by NTGT. Little to no morphological changes were observed in the myometrium of female nudes. The delay in the age of vaginal opening that occurs in athymic nudes was significantly prevented by NTGT. Our results suggest that thymulin plays a relevant physiologic role in the thymus-hypothalamo-pituitary-gonadal axis.